Association of erythropoietin resistance and fibroblast growth factor 23 in dialysis patients: Results from the Japanese Dialysis Outcomes and Practice Patterns Study. Issue 1 (20th August 2020) - Usui, Tomoko; Zhao, Junhui; Fuller, Douglas S.; Hanafusa, Norio; Hasegawa, Takeshi; Fujino, Hiroshi; Nomura, Takanobu; Zee, Jarcy; Young, Eric; Robinson, Bruce M.; Nangaku, Masaomi
Abstract: Background: Fibroblast growth factor 23 (FGF23) plays an important role in chronic kidney disease (CKD)‐related mineral and bone disorders. High FGF23 levels are associated with increased risk of anaemia in non‐haemodialysis CKD patients. FGF23 also negatively regulates erythropoiesis in mice. We hypothesized that higher FGF23 levels are associated with increased erythropoietin hyporesponsiveness among haemodialysis patients. Methods: The study included 1044 patients from the Japanese Dialysis Outcomes and Practice Patterns Study (J‐DOPPS) phase 5 (2012‐2015). The outcome was erythropoiesis‐stimulating agent hyporesponsiveness (ESA‐hypo), defined as mean Hgb <10 g/dL and standardized mean ESA dose >6000 u/week over 4 months following FGF23 measurement. The association between ESA‐hypo and FGF23 was estimated using multivariable‐adjusted logistic generalized estimating equation regression models. Results: Patients with higher levels of FGF23 were younger and had higher levels of serum albumin, creatinine, albumin‐corrected calcium, phosphorus, PTH, 25(OH)‐vitamin D, and had higher percentages of intravenous (IV) iron, IV vitamin D and cinacalcet use. ESA‐hypo was present in 144 patients (13.8%). Compared with the third quintile of FGF23 levels, the odds ratio (95% CI) of ESA‐hypo was 2.14 (0.99, 4.62) and 1.74 (0.74, 4.11) for the first and fifth quintiles, respectively. Conclusion: The lowest and highest levels of FGF23 were associated with higher odds of ESA‐hypo in patients on maintenance haemodialysis, although the associations were not statistically significant. The relationship between FGF23 and anaemia, and particularly the increased risks of ESA‐hypo at low FGF23 levels which might be the result of energy saving, must be confirmed in larger clinical studies. SUMMARY AT A GLANCE: The study included 1044 patients in Japan from J‐DOPPS and found that the lowest and highest levels of serum FGF‐23 were associated with increased odds of ESA‐hyporesponsiveness in patients on maintenance haemodialysis, though this did not reach statistical significance. Further study is needed to address the relationship between circulating FGF‐23 and anaemia in dialysis patients.